2014
DOI: 10.3109/09553002.2014.942014
|View full text |Cite
|
Sign up to set email alerts
|

Potential implications of the bystander effect on TCP and EUD when considering target volume dose heterogeneity

Abstract: In terms of EUD and TCP, the bystander model demonstrates the potential to deviate from the common local LQ model predictions as dose heterogeneity through a prostate CTV varies. The results suggest, at least in a limiting sense, the potential for allowing some degree of dose heterogeneity within a CTV, although further investigation of the assumptions of the bystander model are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Increasing CTV maximum dose has resulted in higher EUDs and TCPs 21 22 Balderson et al 23 have also showed that large amount of target volume IHs is clinically acceptable. Considering our findings, the TCP values of target volume had just slightly lower values at lower priorities, but the NTCP values of bladder and rectum had lower values due to decreasing doses delivered to them.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing CTV maximum dose has resulted in higher EUDs and TCPs 21 22 Balderson et al 23 have also showed that large amount of target volume IHs is clinically acceptable. Considering our findings, the TCP values of target volume had just slightly lower values at lower priorities, but the NTCP values of bladder and rectum had lower values due to decreasing doses delivered to them.…”
Section: Discussionmentioning
confidence: 99%
“…Goitein came up with the idea that delivering higher dose to a portion of the target volume could increase TCP 7. Balderson et al 28. investigated heterogeneous doses through a prostate PTV with modeling work that incorporated a bystander effect model derived from in vitro experiments,29 and concluded that a large amount of dose heterogeneity (a standard deviation of 10 Gy about a mean of 78 Gy) through a prostate target volume could be clinically acceptable, and a moderate amount may even be optimal in terms of EUD and TCP.…”
Section: Discussionmentioning
confidence: 99%
“…Bystander effects have been shown in many different experiments, and these effects are well documented (Nagasawa and Little 1992, Prise and O'Sullivan 2009, Ebert et al 2010, Balderson and Kirkby 2014, Balderson and Kirkby 2015. Bystander effects seem to challenge the fundamental assumption of the prevalent LQ model (i.e.…”
Section: Bystander Effectsmentioning
confidence: 99%